Central mechanisms of cardiovascular regulation during exercise: Integrative functions of the nucleus of the solitary tract - Hidefumi Waki (Japanese Society of Physical Fitness and Sports Medicine, 2012)
Generally, a single bout of exercise induces a moderate increase in arterial pressure (AP) with marked tachycardia as a result of sympathoexcitation which induces vasoconstriction in the major organs, but not in skeletal muscles, and activates heart function. In this review, the potential brain mechanisms underlying cardiovascular regulation during exercise are introduced, with a focus on the functions of the nucleus of the solitary tract (NTS), which is the central termination site of baroreceptor inputs. During a single bout of exercise, neuronal signals from the central command, mediated by the hypothalamus, as well as those from the muscle receptors, are directly or indirectly projected to the NTS and rostral ventrolateral medulla (RVLM). The signals to the RVLM activate sympathetic premotor neurons that, in turn, induce pressor and tachycardiac responses. However, in the absence of resetting of the baroreceptor reflex to a higher pressure range, sympathoexcitation would be dampened and parasympathetic nerves would be excited by heightened levels of baroreceptor inputs, resulting in the attenuation of continuous increases in AP and heart rate. The GABAergic inter-neurons within the NTS may be involved in baroreceptor reflex resetting by limiting the degree of excitation of barosensitive NTS neurons, and thus are capable of 'continuous' increases in sympathetic nerve activity. Among the central command mechanisms, the dorsomedial hypothalamus, hypothalamic paraventricular nucleus, and tuberomammillary nucleus of the posterior hypothalamus may be involved in the GABA-mediated inhibition of NTS functions. Although the recent findings of the central regulatory mechanisms are remarkable, they may provide only a partial explanation of the mechanisms. Since maintaining cardiovascular homeostasis is essential for high exercise performance, further investigations will be required to clarify all aspects of the central regulatory mechanisms underlying cardiovascular responses during exercise.